11.51 Introducing atraumatic needles to the neurology ambulatory day case unit – a quality improvement project. Issue 12 (14th November 2019) - White, Daniel; Scotton, Will; Shah, Zohra; Nakornchai, Tagore; Critchlow, Tamsin; Mitchell, James; Sinclair, Alex; Woolmore, John
Abstract : Introduction: Atraumatic needles are associated with a decreased incidence of postdural-puncture headache. They also reduce the need for additional treatment and have similar efficacy to conventional needles. The aim of this Quality Improvement Project (QIP) was to encourage the use of atraumatic needles in Neurology ambulatory care by developing a sustainable Lumbar Puncture (LP) training method. Methods: A specialised atraumatic needle training video was guru.kumar@nhs.net created for junior doctors starting in Neurology. This accompanied further teaching and opportunities to practice LPs on a simulation mannequin under supervision. Atraumatic needles were added to standard stock and supply was ensured. Two audit cycles recorded the number of LPs performed using an atraumatic needle. Patient age, body mass index, length of stay, pain experienced and any need for image guidance were also recoded. Junior doctor confidence was measured before and after training. Results: 81 LPs were performed in the first cycle, 83 in the second. Atraumatic needle use increased from 26% to 50% between cycles. Junior doctor confidence increased with training from 2/10 to 8/10 (p=0.02). Conclusions: Dedicated induction teaching and observed simulation practice increased junior doctors' confidence in, and frequency of, the use of atraumatic needles.